EXPLORING THE MEDICINAL POTENTIAL OF GUAVA (Psidium guajava guajava) FOR HEALTH AND WELLNESS TH AND WELLNESS - SOWJANYA MGS; MURALI B; RAMESH B (The Bioscan, 2024)
The global escalation of chronic degenerative diseases, often associated with foodborne illnesses, has led to heightened healthcare costs and a diminished quality of life. Consuming foods rich in bioactive substances, such as fruits, vegetables, and seeds, can help reduce the risk factors for developing certain diseases. Psidium guajava, well known for its exquisite flavor, has also been the subject of much research due to its possible health advantages. These benefits include anti-inflammatory, anti-cancer, anti-diabetic, antimicrobial, anti-diarrheal, and anti-hypertensive properties. However, using guava as a therapeutic plant has drawbacks and restrictions. This review sheds light on the relevance of guava in promoting health and wellness by emphasizing the necessity of comprehending the medicinal value of guava and its possible uses. Future investigations into the medicinal potential of guava may result in cutting-edge medical tactics.